The contribution of diseases to the male-female disability-survival paradox in the very old: results from the Newcastle 85+ study. - Andrew Kingston (Public Library of Science (PLoS), 2014)
Background Explanations for the male-female disability-survival paradox - that woman live longer than men but with more disability - include sex differences in diseases and their impact on disability and death. Less is known about the paradox in the very old. We examine sex differences in the presence and impact of disabling and fatal diseases accounting for the male-female disability-survival paradox in very late life. Methods We use data from the Newcastle 85+ Study, a cohort of people born in 1921 and all recruited at age 85 in 2006. Participants underwent a health assessment (HA) at baseline, 18 months, 36 months, 60 months, and a review of their GP records (GPRR) at baseline and 36 months. We used multi-state modelling to assess the impact of specific diseases on disability and death. Disability (measured via ADLs/IADLs) was categorised as no disability (difficulty with 0 activities), or disabled (difficulty with one or more activities). Diseases were ascertained from review of general practice records and cognitive impairment which was defined as an sMMSE of 21 or less (from health assessment). Results In participants who had complete HA and GPRR, women had more arthritis (RR = 1.2, 95% CI: 1.1-1.3) and hypertension (RR = 1.2, 95%CI 1.0-1.3), more disability, and were more likely disabled at all follow-ups. From multistate models, women with cerebrovascular disease (HR: 2.6, 95% CI: 2.1-3.4) or respiratory disease (HR: 2.0, 95% CI: 1.4-3.0) were more likely to become disabled than those without but this did not hold for men (sex difference p<0.01). Men were more likely to die from respiratory disease (HR: 2.2, 95% CI: 1.8-2.8) but this did not hold for women (p = 0.002). Conclusion The disability-survival paradox was still evident at age 85 and appears due to sex differences in the types of diseases and their impact on the disability pathway.